Creating and Validating a DNA Methylation-Based Proxy for Interleukin-6. (17th February 2021) - Stevenson, Anna J; Gadd, Danni A; Hillary, Robert F; McCartney, Daniel L; Campbell, Archie; Walker, Rosie M; Evans, Kathryn L; Harris, Sarah E; Spires-Jones, Tara L; McRae, Allan F; Visscher, Peter M; McIntosh, Andrew M; et al.
Abstract: Background: Studies evaluating the relationship between chronic inflammation and cognitive functioning have produced heterogeneous results. A potential reason for this is the variability of inflammatory mediators which could lead to misclassifications of individuals' persisting levels of inflammation. DNA methylation (DNAm) has shown utility in indexing environmental exposures and could be leveraged to provide proxy signatures of chronic inflammation. Method: We conducted an elastic net regression of interleukin-6 (IL-6) in a cohort of 875 older adults (Lothian Birth Cohort 1936; mean age: 70 years) to develop a DNAm-based predictor. The predictor was tested in an independent cohort (Generation Scotland; N = 7028 [417 with measured IL-6], mean age: 51 years). Results: A weighted score from 35 CpG sites optimally predicted IL-6 in the independent test set (Generation Scotland; R 2 = 4.4%, p = 2.1 × 10 −5 ). In the independent test cohort, both measured IL-6 and the DNAm proxy increased with age (serum IL-6: n = 417, β = 0.02, SE = 0.004, p = 1.3 × 10 −7 ; DNAm IL-6 score: N = 7028, β = 0.02, SE = 0.0009, p < 2 × 10 −16 ). Serum IL-6 did not associate with cognitive ability ( n = 417, β = −0.06, SE = 0.05, p = .19); however, an inverse association was identified between the DNAm score and cognitive functioning ( N = 7028, β = −0.16, SE = 0.02, p FDR < 2 × 10 −16 ). Conclusions: These results suggest methylation-based predictors can be used as proxies for inflammatory markers, potentially allowing for further insight into the relationship between inflammation and pertinent health outcomes.